Tensile properties, biodegradability and bioactivity of thermoplastic starch (TPS)/bioglass composites for bone tissue engineering - Syed Nuzul Fadzli Syed Adam,; Azlin Fazlina Osman,; Roslinda Shamsudin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Composite fabricated from the combination of biodegradable polymer and bioactive filler is beneficial for bone tissue engineering if the biomaterial can perform similar characteristics of the natural inorganic-organic structures of bone. In this study, we have investigated the thermoplastic starch (TPS)/sol-gel derived bioglass composite as new biomaterial for bone tissue engineering. The composites were produced using selected TPS/bioglass mass ratio of 100/0, 95/5, 90/10, 85/15 and 80/20 by a combination of solvent casting and salt leaching techniques. Tensile test results showed the addition of bioglass increased the tensile strength and Young’s modulus, but reduced the elongation at break of the samples. The modulus of all samples were higher than the requirement for cancellous bone (10-20 MPa). The SEM imaging showed the presence of porous structure on the surface of all samples. XRD results confirmed the formation of hydroxycarbonate apatite (HCA) layer on the surface of bioglass containing samples; indicating the occurrence of surface reactions when the samples were immersed in Simulated Body Fluid (SBF). Furthermore, the presence of P-O stretch band in FTIR spectrum between 1000 and 1150 cm-1 and Si-O-Si stretch band at 1000 cm-1 also proved the bioactivity of TPS/bioglass composite. The in vitro biodegradability analysis shows the biodegradability of TPS/bioglass composite decreases with increasing mass ratio of the bioglass.